In-vitro anticancer activity in the gonad extract of Stomopneusres variolaris on HeLa Cells - S. Motch Arockia Vinista,; Jemma Hermelin Jesy Diaz, (The Bioscan, 2026)
The present study was carried out to assess the anticancer activity of gonad extract of Stomopneustes variolaris for cell proliferation and cytotoxicity on HeLa (Human cervix adenocarcinoma cell line) cells at different concentration (10, 25, 50, 100, 200, 500µg/ml). A maximum of 60% toxicity was observed at 500µg/ml and a minimum of 3% at 10 µg. The cell viability of gonad extract ranges from 40% (500µg/ml) to 97% (10µg/ml). The percentage of toxicity increased with increasing concentration of gonad extract. The result suggest that the extract of sea urchin gonad can be considered as a valuable source as therapeutic agents against human cervical cancer. Keywords Stomopneustes variolaris, gonad extract, HeLa cells, toxicity, therapeutic.